Uji Kadar Gula pada Susu Meal Replacement di Kota Medan dengan Spektofotometri UV-Vis - Marini Marini; Rena Meutia; Astriani Natalia; Nerly Juli Pranita Simanjuntak (STIKes Ibnu Sina Ajibarang, 2025)
Diabetes and obesity are closely related, with obesity as a nutritional problem that continues to increase. Obesity occurs due to an imbalance in energy intake and expenditure, while diabetes is often not realized until serious complications appear. A diet high in fiber and low in sugar can reduce the risk of diabetes. Meal replacements such as powdered milk and snack bars can be used, but consumption needs to be limited because their nutritional content is less than ideal and has the potential to cause health problems if consumed excessively. The research was carried out using quantitative and qualitative methods on 3 types of meal replacement milk powder drinks, namely brand A, brand B and brand C. This was done by collecting samples deliberately according to the inclusion and exclusion criteria, which is the sampling strategy used in this research. then research evaluation carried out 3 types of tests; Molisch's test, Benedict's test and Fehling's test. The results of the research show that the three samples of meal replacement milk circulating in the city of Medan contain sugar, but are quite safe for consumption in general and the sugar content in meal replacement milk does not exceed the daily sugar level.